Designing and Applying Adaptation Patterns Embedded in the Script - Ronen, M.; Kohen-Vacs, D. (2009 International Conference on Intelligent Networking and Collaborative Systems, 2009)
CeLS is a web-based system designed to enable teachers and researchers to create, enact and test multi-stage CSCL scripts in actual educational settings. The paper presents CeLS approach and potential for adaptive collaboration scripting, aimed to tailor the activity according to students' performance, personal characteristics and preferences. We specifically focus on two aspects: 'on the fly' adaptations according to enactment events and Adaptation Patterns: pre-designed processes that are embedded in the script definition.